Normative Approach to the Prohibition of Euthanasia in Indonesian Law and Islamic Law - Emirza Nur Wicaksono; Dinda Maurizka Azura (Ius Poenale, 2025)
Euthanasia is an issue in bioethics that remains debatable between medical ethics, human rights, and religious principles. In Indonesia, the lack of explicit regulation and the strong influence of moral and religious values create legal ambiguity and ethical uncertainty for healthcare providers. This study examines the normative foundations of euthanasia prohibition in Indonesian positive law and Islamic law, highlighting their shared commitment to the sanctity of life but differing philosophical bases. Indonesian law, rooted in constitutional and criminal provisions, treats euthanasia as an unlawful act, while Islamic law prohibits it on theological grounds, allowing limited withdrawal of treatment under strict conditions. The study underscores the need for a coherent national framework that harmonizes constitutional, ethical, and religious values to guide future health law and bioethics policy in Indonesia.